Strategic Management of Kiai Leadership in The Empowerment of Pondok Pesantren Through Community Work Training Center Program as An Effort to Increase Santri Independence - Juhara, Jaja; Sofyan Sauri; Deti Rostini; Faiz Karim Fatkhullah (International Journal of Educational Research & Social Sciences, 2022)
Management and leadership are closely related to the graduates that will be produced, namely giving birth to students, who are able to combine scientific and empirical theorists in the field. The high quality of the education process in boarding schools is seen from how the management is controlled by the leadership of kiai as a caregiver, leader and at the same time the owner of pesanten hut. However, the fact is that graduates of boarding schools are still one of the unemployed due to the lack of skills gained when studying in boarding schools. Whereas pondok pesantren as one of the educational institutions has enormous potential in improving the standard of living of the community. The problem of unemployment that plagues the majority of Muslims stems not only from the problem of intelligence, but also the problem of life skills, because with life skills helps humans be able to survive in living life and achieve what they want, and vice versa. The purpose of the research is to describe strategic management of kiai leadership, planning, priority programs, evaluations, as well as constraints and solutions in the empowerment of boarding schools as an effort to increase the independence of santri This research applies a qualitative approach with the type of case study research with multisitus design. Data is collected by conducting in-depth interviews, participant observations and documentation studies. Data analysis uses data reduction, data presentation and conclusion withdrawal. Techniques to check the validity of research findings through trianggulation of data sources and data collection techniques. The results showed that the strategic management of kiai leadership in the empowerment of pesantren huts has not fully run in accordance with planning, empowerment priority program policies by opening pesanten cottage business units, including: kopontren, BMT, carpentry, livestock, agroindustry, mebeuler, and convection, and empowerment evaluation is carried out at the stage before implementation, activity process and results of activities. Kedala in empowerment including strategies based more on the wishes of kiai, has not touched on the needs of the students, the socialization of the program has not been maximal, the santri has not been maximally actively played in the program carried out, the limited human resources (HR) of the manager of the boarding school are qualified, the discipline and commitment of the students has not been optimal.